PRIMARY SCHOOL TEACHERS’ TENDENCY TO BECOME A MANAGER: SAMPLE OF GAZIANTEP PROVINCE (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Education has been a crucial process which has a significant role in the lifetime of individuals and societies since the ancient times and considered to be the system which enables economic, political and social system to be sustained. The fact that education system is important in terms of both education and economy necessitates large-scale investments and availability of substantive financial resources for education service to be provided. This imperative requires efficient management of primary schools in many countries in which public funding of education is at present. Efficient management of primary schools depends on school principals. In certain countries, principal may be someone out of school although in other countries as Turkey, teachers may become principals. To what extend can principals help the school, teachers, students and their environment? Analyzing the primary school teachers tendency to become principal is of vital importance in terms of contributing the possible studies which will be conducted. Main purpose of this study is to determine whether or not primary school teachers tendency to become a principal varies according to gender, age, graduation grade and period of service. In the study, a survey was conducted to 486 primary school teachers who worked in Gaziantep in 2012 2013 school year under general survey model. In consequence of the study, it is observed that personal tendency to become a manager changes by gender.